Clusters of Health-Related Social Needs Among Adult Primary Care Patients - Vest, Joshua R.; Wu, Wei; Conner, Kyaien (Journal of the American Board of Family Medicine, 2025)
Patients frequently report multiple health-related social needs (HRSNs) at the same time. This study aimed to identify clusters of co-occurring HRSNs in an adult primary care population. We surveyed 1252 adult (>=18) primary care patients in Indianapolis, IN. Subjects completed surveys in person at 1 of 3 sites operated by 2 different health systems. Data collection was offered in both English and Spanish. Surveys comprised previously published and validated instruments covering housing instability, financial strain, food insecurity, transportation barriers, unemployment, and legal problems. We identified 4 underlying clusters of HRSNs within the patient population using Complete-Linkage Agglomerative Hierarchical Clustering: "low HRSNs" (38.6%), "high HRSNs" (29.6%), "housing dominant" (23.2%), and "food dominant" (8.6%). The high HRSNs cluster had higher average comorbidity scores ( < .001), number of inpatient admissions ( = .004), number of ED visits ( < .001), and number of primary care visits ( < .001). As health care organizations increasingly focus on HRSNs as an approach to reducing costs and improving health of patients, these findings indicate that organizational strategies and actions should consider the interrelated and co-occurring nature of HRSNs. To support a large number of patients, strategies should support multiple HRSNs.